How light, temperature, and measurement and growth [CO2] interactively control isoprene emission in hybrid aspen - Niinemets, Ülo (Journal of experimental botany, 2015)
© The Author 2014. Published by Oxford University Press on behalf of the Society for Experimental Biology.